Division of labor within the DNA damage tolerance system reveals non-epistatic and clinically actionable targets for precision cancer medicine. Issue 13 (12th July 2022) - Spanjaard, Aldo; Shah, Ronak; de Groot, Daniël; Buoninfante, Olimpia Alessandra; Morris, Ben; Lieftink, Cor; Pritchard, Colin; Zürcher, Lisa M; Ormel, Shirley; Catsman, Joyce J I; de Korte-Grimmerink, Renske; Siteur, Bjørn; et al.
Abstract: Crosslink repair depends on the Fanconi anemia pathway and translesion synthesis polymerases that replicate over unhooked crosslinks. Translesion synthesis is regulated via ubiquitination of PCNA, and independently via translesion synthesis polymerase REV1. The division of labor between PCNA-ubiquitination and REV1 in interstrand crosslink repair is unclear. Inhibition of either of these pathways has been proposed as a strategy to increase cytotoxicity of platinating agents in cancer treatment. Here, we defined the importance of PCNA-ubiquitination and REV1 for DNA in mammalian ICL repair. In mice, loss of PCNA-ubiquitination, but not REV1, resulted in germ cell defects and hypersensitivity to cisplatin. Loss of PCNA-ubiquitination, but not REV1 sensitized mammalian cancer cell lines to cisplatin. We identify polymerase Kappa as essential in tolerating DNA damage-induced lesions, in particular cisplatin lesions. Polk- deficient tumors were controlled by cisplatin treatment and it significantly delayed tumor outgrowth and increased overall survival of tumor bearing mice. Our results indicate that PCNA-ubiquitination and REV1 play distinct roles in DNA damage tolerance. Moreover, our results highlight POLK as a critical TLS polymerase in tolerating multiple genotoxic lesions, including cisplatin lesions. The relative frequent loss of Polk in cancers indicates an exploitable vulnerability for precision cancer medicine. Graphical Abstract: